2015
DOI: 10.14214/sf.1265
|View full text |Cite
|
Sign up to set email alerts
|

Soil and soil-water chemistry below different amounts of logging residues at two harvested forest sites in Sweden

Abstract: Logging residues (LR),i.e. tops, branches, and needles, are increasingly being harvested for energy production in Fennoscandia. These residues are temporarily piled on site awaiting transport. This study was undertaken to investigate effects on the soil and soil-water chemistry below different amounts of LR at two recently harvested coniferous sites in Sweden. Seven treatments were included and the studied amounts of LR ranged from no LR left on the ground to four times the estimated LR amount of the harvested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…The nutrient concentration often returns to pre-cutting levels within relatively short time, normally 3-5 years, especially if clear-cut is performed without any other disturbances (Raulund-Rasmussen et al, 2011). Even if soil-water chemistry is affected by the residue treatments, the response tends to differ between the sites (Ring et al, 2015). We detected a strong response in nutrient concentrations following regeneration felling in the all three sites (except SOH plot in Oxalidosa turf.…”
Section: Resultsmentioning
confidence: 73%
“…The nutrient concentration often returns to pre-cutting levels within relatively short time, normally 3-5 years, especially if clear-cut is performed without any other disturbances (Raulund-Rasmussen et al, 2011). Even if soil-water chemistry is affected by the residue treatments, the response tends to differ between the sites (Ring et al, 2015). We detected a strong response in nutrient concentrations following regeneration felling in the all three sites (except SOH plot in Oxalidosa turf.…”
Section: Resultsmentioning
confidence: 73%
“…Ring et al (2016) demonstrated in an experiment lower NO 3 concentrations in soil solution after whole-tree harvesting than after conventional harvesting. In Ring et al (2015) one of the two investigated sites showed decreasing NO 3 concentrations with decreasing amount of logging residues left on the clearcuts, whereas the other showed no such tendency. de Jong et al (2017) concluded in a synthesis article that whole-tree harvesting leads to no or a slightly decreased risk of N leaching.…”
Section: Discussionmentioning
confidence: 78%
“…The pH was analysed to indicate possible impacts on nitrification by which H + is produced along with NO 3 -(cf. Ring et al 2015). Furthermore, changes in pH may affect the leaching of Al and Cd (Berggren 1992;Bergkvist 2001).…”
Section: Introductionmentioning
confidence: 99%